Tajemnice Liberty Island. Rozmowy z wolnością .......... 361 - Pękala, Bożena (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
THE SECRETS OF LIBERTY ISLAND: WHISPERS WITH FREEDOMThis work is a piece of literary fiction.The Secrets of Liberty Island: Whispers with Freedom is a poetic and reflective narrative that personifies the Statue of Liberty as both observer and participant in the historical and cultural transformations of the modern world. Blending fictional storytelling with real historical contexts, the narrative centers on a symbolic and intimate exchange between the Statue and a visiting Polish sociologist in the 1980s. Through their whispered dialogues under the stars, the story explores profound themes such as freedom, identity, cultural memory, and the ever-evolving relationship between nations—particularly the United States and France. The Statue emerges as a timeless witness to humanity’s struggles, hopes, and contradictions, offering insight into the fragile, shifting nature of liberty and the enduring need for understanding across generations and borders.